The coinage of Herod Antipas: a study and die classification of the earliest coins of Galilee - Kogon, Aaron J. (Ancient Judaism and early Christianity, 2018)
"The Coinage of Herod Antipas provides a comprehensive, multifaceted and up-to-date re-examination of the coins of Herod Antipas, the tetrarch of Galilee and Peraea between 4/3 BCE and 39/40 CE. Kogon and Fontanille classify about 800 coins by obverse and reverse dies. From this die classification they generate, for the first time ever for this tetrarch, about 300 composite die images. In addition, the authors examine both technical aspects of the coins (e.g. metrology, mint output) and non-technical aspects (e.g. inscriptions, iconography). They also review the geographic distribution of provenanced coins. Through this analysis of the coins of Herod Antipas, Kogon and Fontanille provide a greater understanding of the Sitz im Leben of first century Galilee."--Provided by publisher